Estimation of the worldwide seroprevalence of cytomegalovirus: A systematic review and meta‐analysis. (31st January 2019) - Zuhair, Mohamed; Smit, G. Suzanne A.; Wallis, Gabriel; Jabbar, Faiz; Smith, Colette; Devleesschauwer, Brecht; Griffiths, Paul
Summary: Cytomegalovirus (CMV) infection does not usually produce symptoms when it causes primary infection, reinfection, or reactivation because these three types of infection are all controlled by the normal immune system. However, CMV becomes an important pathogen in individuals whose immune system is immature or compromised, such as the unborn child. Several vaccines against CMV are currently in clinical trials that aim to induce immunity in seronegative individuals and/or to boost the immunity of those with prior natural infection (seropositives). To facilitate estimation of the burden of disease and the need for vaccines that induce de novo immune responses or that boost pre‐existing immunity to CMV, we conducted a systematic survey of the published literature to describe the global seroprevalence of CMV IgG antibodies. We estimated a global CMV seroprevalence of 83% (95%UI: 78‐88) in the general population, 86% (95%UI: 83‐89) in women of childbearing age, and 86% (95%UI: 82‐89) in donors of blood or organs. For each of these three groups, the highest seroprevalence was seen in the World Health Organisation (WHO) Eastern Mediterranean region 90% (95%UI: 85‐94) and the lowest in WHO European region 66% (95%UI: 56‐74). These estimates of the worldwide CMV distribution will help develop national and regional burden of disease models and inform future vaccine development efforts.